Analysis of Human Factors Influencing Error Occurrence Using RCA and HFACS-OGI in a Gas Company - sara boroun; Reza gholamnia; Mousa Jabari (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: Human factors are central and vital issues in different working environments, including industries. The operational processes of a gas company are among the processes in which several accidents have occurred. Accidents are of the most important causes of direct and indirect costs to the industry, so it is necessary to identify the human factors which have the greatest effect on the occurrence of errors regarding accidents, recognize them, and adopt control and preventive strategies to prevent them from happening again. Accordingly, the study of human factors affecting error occurrence is of great importance in industry. Therefore, this study aimed to analyze the human factors affecting the occurrence of errors in the operational processes of the gas companies. Method: This was a descriptive cross-sectional study conducted in a gas company. Statistics and documents of the accidents from a 10-year period in the gas company were received from the HSE (Health and Safety Executive) of this center, and examined and analyzed through the methods of human factor analysis and system classification for the oil and gas industry (HFACS-OGI) and root cause analysis (RCA). Results: The results of applying HFACS-OGI method showed that in level one, error section, subgroup of "perceptual error" ; in level two, subgroup of "human resource management"; in level three, "inadequate supervision"; in level 4, "safety culture" section ;and at level 5, the "legal framework" had the highest percentage. Through the RCA method, the highest frequency was for defects related to work requirements and the lowest frequency was related to disqualification. Conclusion: Human factors affecting the occurrence of error include cognitive and behavioral characteristics of employees, defects in the operational processes of safety management system, inadequate and proper supervision, lack of/deficiency in training and the employees' practical experience, non-compliance with general safety principles, lack of/deficiency in implementation of control measures regarding the management of the risks approved by the organization , the lack of/defect in the optimal implementation of human resource management, which can be reduced by improving the performance indicators, executive procedures, proper planning, providing  monitoring courses ,and proper supervision .Finally, it was found that HFACS-OGI and RCA methods can be used in similar working environments due to their consistency in presenting the results.